The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1089/scd.1.1995.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor Expansion of Human Bone Marrow: Comparison of Unprocessed, Density-Separated, and CD34-Enriched Cells

Abstract: Scale-up of human hematopoietic cultures was previously described in continuously perfused systems with bone marrow mononuclear cells (BMMNC), yielding expansion of both progenitors and long-term culture-initiating cells (LTC-IC). We report here on the use of these systems for expansion of unprocessed whole BM cells (WBMC) and CD34-enriched cells. Density separation recovered 84% of CFU-GM and 65% of LTC-IC from WBMC. Subsequent CD34 selection recovered 17% of CFU-GM and 48% of LTC-IC from the MNC fraction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…[24][25][26][110][111][112][113][114] These systems were designed to allow larger volumes as well as to provide improved nutrient delivery and gas exchange. The secreted products of mature granulocytes and macrophages are toxic to progenitors, 115 and mature macrophages can directly damage cultured stroma and hematopoietic pro-genitors.…”
Section: Continuous Perfusion Culture Systemsmentioning
confidence: 99%
“…[24][25][26][110][111][112][113][114] These systems were designed to allow larger volumes as well as to provide improved nutrient delivery and gas exchange. The secreted products of mature granulocytes and macrophages are toxic to progenitors, 115 and mature macrophages can directly damage cultured stroma and hematopoietic pro-genitors.…”
Section: Continuous Perfusion Culture Systemsmentioning
confidence: 99%
“…16,17,43 Because the accessory cell composition of CB cultures is different from BM cultures (ie lacking an adherent stroma), the presence of mRNA encoding a number of growth factors was assessed by RT-PCR (Figure 7). Surprisingly, transcripts for most growth factors tested (G-CSF, GM-CSF, IL-1␤, IL-6, LIF, KL, FL, Tpo, Growth factor mRNA in bone marrow and cord blood expansion cultures.…”
Section: Endogenous Growth Factor Mrna In Cb and Bm Culturesmentioning
confidence: 99%
“…Most of the recent literature on CB cell expansion has focused on the culture of CD34-enriched cells or subsets thereof. However, perfusion bioreactor systems have been proven capable of expanding non-enriched cells from BM [16][17][18] and mPB, 19 due to their ability to support high density accessory cell populations. 17,20 In fact, in the CB transplant setting, the potential advantages of CD34-enrichment prior to expansion, such as tumor purging and T cell depletion, are less relevant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was a 73% loss of LTC-IC in the CD34 ϩ sample at the same time that total cell number expanded 269-fold. These authors concluded that CD34 ϩ cells can be expanded regardless of the extent of enrichment [32]. In fact, Xiao et al demonstrated that expansion from as little as one CD34 ϩ cell derived from UCB has been shown to occur with maintenance of self-renewal capacity for at least 2 weeks.…”
Section: Selection Of Cd34 ϩ Cells Versus Unselected Cell Populationsmentioning
confidence: 99%